Taking the experience home: an exploration of how brands have used digital transformation to shift brand experience in a crisis. - Paiken, Janine (The IIE, 2020)
The Covid-19 pandemic has resulted in business and brands globally needing to shift their strategies to include digital transformation. Whether it has been learning to work remotely on channels such as Zoom and Microsoft Teams, or needing to change their entire experience offerings to become more digitally inclined, everyone has been affected by the pandemic. This study aimed to explore these changes in terms of how they have been implemented, specifically looking at Virgin Active South Africa, whose business plan relies on consumers exercising in their gyms. Using the sensory marketing model proposed by Bertil Hultén (2009), this shift was explored using our five senses as the method to understand the how. Findings showed that while digital transformation is a reality, there are still limitations to a digital brand experience in terms of expressing sensory connections. Taste, touch, and smell still need to be explored deeper to find ways to incorporate them into a digital experience. A limitation to the model was that it excludes the emotional connection between consumer and brand – a vital characteristic in brand experience. This is a potential study that can be conducted in the future.
Keywords: Virgin Active, South Africa; Emotional connection; Gym; Exercise; Consumer behaviour